A liquid thermoelectric device composed of organic solution. (1st May 2022) - Wake, Akihiro; Inoue, Dai; Moritomo, Yutaka
Abstract: The liquid thermoelectric device (LTE) exhibits a very simple structure that consists of hot/cold electrodes of identical type and a solution with a redox couple. Here, we evaluated the performances of LTE composed of acetone (or acetonitrile) solutions of Fe(ClO4 )2 /Fe(ClO4 )3 against their concentration ( m ). The electrochemical Seebeck coefficients ( α ) of organic LTE range from 1.5 to 2.5 mV K −1 and are higher than α (=1.4 mV K −1 ) of the corresponding aqueous LTE. The dimensionless figure of merit (ZT) of organic LTE is ≈0.015 at maximum and is higher than the maximum ZT (=0.009) of the corresponding aqueous LTE. Thus, the organic LTE is promising as an energy harvesting device.